Reservoir Characterization and Petrophysical Evaluation for Paleogene Khurmala Formation in Northern Iraq - Abdula, Rzger Abdulkarim; Shwani, Ayub M.; Abid, Parween R.; Simisi, Bienfait K. (Journal of Petroleum Research and Studies, 2025)
This study presents a detailed reservoir characterization and petrophysical evaluation of the Paleogene Khurmala Formation within the X Oilfield, northern Iraq. The analysis is based on digitized well log data, including density, neutron porosity, gamma ray, and resistivity logs, processed using Neuralog and Techlog 2018 software. Lithology was determined through neutron-density cross plots, confirming the presence of heterogeneous carbonate sequences consisting of dolomite and limestone. Shale volume was calculated using gamma ray logs, revealing localized shale enrichment in parts of the formation. Effective porosity was derived by correcting density and neutron porosity logs for shale influence, while permeability was estimated through porosity-permeability relationships. Water saturation was calculated using Archie’s equation, indicating that large portions of the formation are water-saturated with low hydrocarbon potential, except for one zone (RU-3) which demonstrates favorable reservoir characteristics. The formation was divided into four reservoir units based on variations in shale content, porosity, water saturation, and permeability. RU-3 exhibited the best petrophysical properties, with high porosity, low water saturation, and minimal shale content, making it the most promising target for hydrocarbon production. The results provide valuable insights for optimizing reservoir management in this field.